2008
DOI: 10.1007/s11081-008-9059-x
|View full text |Cite
|
Sign up to set email alerts
|

A new spanning tree-based genetic algorithm for the design of multi-stage supply chain networks with nonlinear transportation costs

Abstract: The design of configuration and the transportation planning are crucial issues to the effectiveness of multi-stage supply chain networks. The decision makers are interested in the determination the optimal locations of the hubs and the optimal transportation routes to minimize the total costs incurred in the whole system. One may formulate this problem as a 0-1 mixed integer non-linear program though commercial packages are not able to efficiently solve this problem due to its complexity. This study proposes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Abuali et al (1995) proposed the determinant encoding and proved that this code is better than that of Prüfer. Both the works of Chou et al (2001) and Yao and Hsu (2009) on logistic networks further confirmed this conclusion. Wang and Hsu (2010a) proposed a revised spanning tree-based genetic algorithm with determinant encoding that was applied successfully to the closed-loop logistics model.…”
Section: Spanning Tree-based Genetic Algorithmmentioning
confidence: 53%
See 3 more Smart Citations
“…Abuali et al (1995) proposed the determinant encoding and proved that this code is better than that of Prüfer. Both the works of Chou et al (2001) and Yao and Hsu (2009) on logistic networks further confirmed this conclusion. Wang and Hsu (2010a) proposed a revised spanning tree-based genetic algorithm with determinant encoding that was applied successfully to the closed-loop logistics model.…”
Section: Spanning Tree-based Genetic Algorithmmentioning
confidence: 53%
“…However, empirical investigations have shown that Prüfer encoding is an unsatisfactory method for evolutionary algorithms and should therefore be avoided (Yeh 2005). However, the spanning tree-based GAs have the advantage of being capable of using the least number of arcs between two stages to solve logistics problems, thereby saving memory and time (Yao and Hsu 2009). Abuali et al (1995) proposed the determinant encoding and proved that this code is better than that of Prüfer.…”
Section: Spanning Tree-based Genetic Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Many optimization methods have been developed and applied to the models mentioned above. These techniques range from linear programming algorithms to more complex ones such as spanning tree algorithms, evolutionary algorithms, taboo search, simulated annealing, and specific heuristics (Current et al 1987;Lotarev 1989;Klempous et al 1994;Babel and Kellerer 2003;Nepal and Park 2005;Creput and Koukam 2007;Song et al 2007;Sanchez-Silva et al 2009;Unnikrishnan et al 2009;Yao and Hsu 2009).…”
Section: Comparison To Other Domains and Critical Analysismentioning
confidence: 99%